Caracterización de la respuesta de las bombas sodio potasio a los bufadienólidos provenientes de rhinella marina (2024)
Heart failure represents a significant therapeutic challenge, due to the limited efficacy and safety of traditional drugs like digitalis. Bufadienolides, cardiotonic steroids present in the venom of the amphibian Rhinella marina, have emerged as a promising alternative due to their ability to modulate the activity of Na/K-ATPase pumps and improve cardiac function. The objective of this study was to evaluate the dose-response of Na/K-ATPase pumps to bufadienolides and methyldigoxin (reference drug) using electrical impedance spectroscopy (EIS). For this, an RC circuit was built to validate the bioelectrical impedance measurement system. Solutions of bufadienolides and methyldigoxin were prepared at different concentrations, and the response of Na/K ATPase pumps in Eleutherodactylus johnstonei biomodels was characterized by electrical impedance spectroscopy (EIS) using an Ussing chamber. The RC circuit correctly emulated the epithelial behavior of the biomodel, validating the methodology. Furthermore, as the concentration of bufadienolides and methyldigoxin increased, a rightward shift was observed in the bioelectrical impedance curves, suggesting a specific interaction with the Na/K pumps and a modulation of their activity. These results support the premise that bufadienolides interact similarly to digitalis and could represent a source of information for new treatments, but further research is required to understand the specific mechanisms and evaluate their pharmacological profile.